Flux Cored Wire

The flux-containing wire for gas shielded arc welding, with optimized components, addresses the challenges of joint performance and creep rupture strength in 9%Cr steel welds by enhancing toughness and workability even at high PWHT temperatures.

JP7658753B2Active Publication Date: 2025-04-08KOBE STEEL LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021021936
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-15
Publication Date
2025-04-08
Estimated Expiration
2041-02-15

AI Technical Summary

Technical Problem

9%Cr steel welds exhibit deterioration in joint performance due to martensitic structure formation during welding, and high-temperature post-weld heat treatment (PWHT) can lead to phase transformation and reduced creep rupture strength if not managed properly.

Method used

A flux-containing wire for gas shielded arc welding is developed, incorporating specific components such as Co, TiO2, Na, and K within defined ranges to suppress residual δ-ferrite, improve toughness, and enhance welding workability even at high PWHT temperatures.

Benefits of technology

The flux-containing wire achieves excellent strength, toughness, and welding workability for 9%Cr steel welds, even at high PWHT temperatures like 760°C, thereby improving joint performance and maintaining creep rupture strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658753000001
    Figure 0007658753000001
  • Figure 0007658753000002
    Figure 0007658753000002
  • Figure 0007658753000003
    Figure 0007658753000003
Patent Text Reader

Abstract

To provide a wire with a flux for gas shield arc-welding that can acquire weld metal having excellent strength and toughness even if a PWHT temperature is a high, and is excellent in welding operability.SOLUTION: A wire with a flux for gas shield arc-welding which has an outer film made of steel filled with fluxes, in which contents of Fe, C, Mn, Cr, Ni, Mo, Nb, V, P and S are controlled to fall in respective predetermined ranges, contains TiO2: 3.0 mass% or more and 9.0 mass% or less, SiO2 reduced values of metal Si and Si compounds: 0.5 mass% or more and 1.5 mass% or less, Co: 0.10 mass% or more and 1.50 mass% or less and N: 0.015 mass% or more and 0.060 mass% or less, and further contains Li: 0.11 mass% or less, Mg: 0.85 mass% or less and total amounts of K and Na: 0.3 mass% or less, with respect to the total mass of the wire.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flux-cored wire. [Background technology]

[0002] In general, 9% Cr steel has excellent high-temperature properties and is used in thermal and nuclear power boilers, pressure vessels, etc. In recent years, there has been an increasing demand for flux-cored wires that can provide weld metals with even better mechanical properties as wires for gas-shielded arc welding to manufacture such welded structures.

[0003] For example, Patent Document 1 discloses a flux-cored wire in which flux is filled into a stainless steel sheath having a Cr content of 11 to 13.5% by weight, and in which the contents of other components such as Ni and Mn are specified within predetermined ranges. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-207490 Summary of the Invention [Problem to be solved by the invention]

[0005] However, 9% Cr steel has high hardenability, and if it is welded as is, both the heat-affected zone and the weld metal will have a martensite structure, which will deteriorate the joint performance. Therefore, in order to remove the welding residual stress and residual hydrogen in the weld, and to soften the weld heat-affected zone and improve the ductility and toughness of the weld by tempering the weld to form a martensite structure, the weld is usually subjected to post-weld heat treatment (PWHT).

[0006] From the viewpoint of residual stress relief, a higher PWHT temperature is advantageous, but the A of the weld metal C1If the weld is welded at a temperature above the transformation point, the weld metal will undergo a phase transformation, and there is a risk that the creep rupture strength will be significantly deteriorated. C1 There is a movement to regulate the upper limit of the total content of Mn and Ni in order to increase the transformation point. C1 Since there is a negative correlation between the transformation point and the total content of Mn and Ni, the application of high-temperature PWHT is inappropriate when the content of these elements is high. Even when the flux-cored wire described in Patent Document 1 is used, the weld metal after PWHT may not have the desired strength, especially when PWHT is performed at a high temperature such as 760°C. Furthermore, Patent Document 1 does not disclose the slag components, and there is room for improvement in the welding workability when performing welding in various positions.

[0007] The present invention has been made in view of the above-mentioned circumstances, and has an object to provide a flux-cored wire for gas-shielded arc welding which is suitably used for welding 9% Cr steel, can provide a weld metal excellent in strength and toughness even at a PWHT temperature as high as, for example, 760°C, and has good welding workability. [Means for solving the problem]

[0008] The inventors of the present invention have conducted extensive research into flux-cored wires for improving the strength and toughness after PWHT, and have found that by adding Co to the flux-cored wire and keeping each component within a specific range, it is possible to suppress the residual δ-ferrite and improve the toughness of the weld metal. Furthermore, as a result of extensive research into all-position welding, it has been found that by keeping the slag components such as TiO2, Na, and K within specific ranges, good welding workability can be obtained even in various positions. The present invention was made based on these findings.

[0009] The above object of the present invention is achieved by the following configuration [1] relating to a flux-cored wire.

[0010] [1] A flux-cored wire for gas-shielded arc welding in which a steel sheath is filled with flux, For the total mass of wire, Fe: 75% by mass or more and 85% by mass or less, C: 0.05% by mass or more and 0.25% by mass or less, TiO2: 3.0% by mass or more and 9.0% by mass or less, Metallic Si and Si compounds in terms of SiO2: 0.5% by mass or more and 1.5% by mass or less, Mn: 0.5% by mass or more and 2.0% by mass or less, Cr: 8.0% by mass or more and 11.0% by mass or less, Ni: 0.05% by mass or more and 1.0% by mass or less, Mo: 0.7% by mass or more and 1.5% by mass or less, Co: 0.10% by mass or more and 1.50% by mass or less, Nb: 0.01% by mass or more and 0.15% by mass or less, V: 0.1% by mass or more and 0.5% by mass or less, N: 0.015% by mass or more and 0.060% by mass or less; Li: 0.11% by mass or less, Mg: 0.85% by mass or less, Total content of K and Na: 0.3 mass% or less, P: 0.020% by mass or less, S: 0.020 mass % or less.

[0011] Further, preferred embodiments of the present invention relating to the flux-cored wire relate to the following [2] to [5]. [2] For the total mass of wire, Contains Li: 0.01% by mass or more and 0.11% by mass or less, The TiO2 content in the wire is expressed as [TiO2] in mass% relative to the total mass of the wire. When the Li content in the wire is expressed as [Li] in mass% relative to the total mass of the wire, The flux-cored wire according to [1], characterized in that [TiO2] / [Li]: 70 or more and 170 or less.

[0012] [3] Furthermore, for the total mass of the wire, The flux-cored wire according to [1] or [2], characterized by containing F: 0.10 mass % or more and 0.60 mass % or less.

[0013] [4] Furthermore, At least one selected from Al2O3, metallic Zr, and a Zr compound is added to the total mass of the wire. Al2O3: 0.50% by mass or less, The flux-cored wire according to any one of [1] to [3], characterized in that the content of metallic Zr and Zr compounds is in the range of 0.50 mass % or less in terms of ZrO2.

[0014] [5] Furthermore, for the total mass of the wire, The flux-cored wire according to any one of [1] to [4], further comprising: Al: 0.20 mass % or less. Effect of the Invention

[0015] According to the present invention, it is possible to provide a flux-cored wire for gas-shielded arc welding that can obtain a weld metal having excellent strength and toughness even at a high PWHT temperature of, for example, 760°C, and that has good welding workability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, the embodiments of the present invention will be described in detail. Note that the present invention is not limited to the embodiments described below, and can be modified and implemented as desired without departing from the gist of the present invention.

[0017] [1. Flux-cored wire] The flux-cored wire according to this embodiment (hereinafter also simply referred to as "wire") has flux filled in a steel outer sheath. Further, the flux-cored wire according to this embodiment is a wire for gas shielded arc welding of so-called low alloy steel plates, and can be suitably used particularly for gas shielded arc welding of 9% Cr steel plates.

[0018] Hereinafter, regarding the components contained in the flux-cored wire according to this embodiment, the reasons for their inclusion and the reasons for limiting the numerical ranges will be explained. In the following description, unless otherwise specified, the amount of each component in the flux-cored wire is defined as the content per total mass of the wire, that is, the total amount of the outer sheath and the flux inside the outer sheath.

[0019] <Fe: 75 mass% or more and 85 mass% or less> Fe is the main component of the wire according to this embodiment. The Fe content with respect to the total mass of the wire is 75 mass% or more, and may be 76 mass% or more or 77 mass% or more. Also, the Fe content with respect to the total mass of the wire is 85 mass% or less, and may be 84 mass% or less or 82 mass% or less.

[0020] <C: 0.05 mass% or more and 0.25 mass% or less> C is an important element that combines with Cr, Mo, V, and Nb to precipitate carbides and has the effect of ensuring the strength of the weld metal. If the C content with respect to the total mass of the wire is less than 0.05 mass%, the desired strength of the weld metal cannot be obtained. Therefore, the C content with respect to the total mass of the wire is 0.05 mass% or more, preferably 0.07 mass% or more, and more preferably 0.09 mass% or more. On the other hand, if the C content with respect to the total mass of the wire exceeds 0.25 mass%, the solidification temperature of the segregation part decreases significantly, and hot cracking is likely to occur. Also, the precipitation of carbides becomes excessive and the toughness of the weld metal decreases. Therefore, the C content with respect to the total mass of the wire is 0.25 mass% or less, preferably 0.23 mass% or less, and more preferably 0.21 mass% or less.

[0021] <TiO2: 3.0 mass% or more and 9.0 mass% or less> TiO2 is a component added to the wire as a slag former and has the effect of improving the weldability. When the TiO2 content based on the total mass of the wire is less than 3.0 mass%, the slag coverage deteriorates. Therefore, the TiO2 content based on the total mass of the wire is 3.0 mass% or more, preferably 4.0 mass% or more, and more preferably 4.5 mass% or more. On the other hand, when the TiO2 content based on the total mass of the wire exceeds 9.0 mass%, the amount of slag generated becomes excessive, and slag entrainment is likely to occur at the welded part. Also, the amount of oxygen in the weld metal increases and the toughness deteriorates. Furthermore, when Ti of TiO2 is excessively contained in the weld metal, the tensile strength becomes excessive and the toughness decreases. Therefore, the TiO2 content based on the total mass of the wire is 9.0 mass% or less, preferably 8.5 mass% or less, and more preferably 8.0 mass% or less. In this embodiment, the TiO2 content is the TiO2 conversion value of the Ti compound. More specifically, the TiO2 content is the value obtained by converting all Ti that is insoluble in acid into TiO2.

[0022] <SiO2 conversion value of metallic Si and Si compound: 0.5 mass% or more and 1.5 mass% or less> Si functions as a deoxidizer for the weld metal, has the effect of reducing the amount of oxygen in the weld metal, and also has the effect of improving the viscosity of the slag, improving the slag coverage, and improving the conformity of the weld termination part. When the SiO2 conversion value based on the total mass of the wire is less than 0.5 mass%, the above effects cannot be obtained sufficiently, and the bead appearance and bead shape deteriorate. Therefore, the SiO2 conversion value based on the total mass of the wire is 0.5 mass% or more, preferably 0.55 mass% or more, and more preferably 0.6 mass% or more. On the one hand, when the SiO2 equivalent value with respect to the total wire mass exceeds 1.5% by mass, slag entrainment is likely to occur in the welded part. Also, Si is a ferrite-forming element, and when added in excess, it causes the residual of δ-ferrite and reduces the toughness of the weld metal. Therefore, the SiO2 equivalent value with respect to the total wire mass should be 1.5% by mass or less, preferably 1.4% by mass or less, and more preferably 1.3% by mass or less. In this embodiment, the SiO2 equivalent value is defined as the SiO2 equivalent value obtained by converting all Si contained in elemental Si, Si alloys, and Si compounds (excluding Si compounds in alloys) contained in the wire into SiO2.

[0023] <Mn: 0.5% by mass or more and 2.0% by mass or less> Mn functions as a deoxidizer for the weld metal, has the effect of improving the strength of the weld metal, and also has the effect of improving toughness. Also, Mn is an austenite-forming element and has the effect of suppressing the deterioration of toughness due to the residual of δ-ferrite in the weld metal. When the Mn content with respect to the total wire mass is less than 0.5% by mass, it causes insufficient deoxidation and cannot sufficiently obtain the effect of suppressing the residual of δ-ferrite, resulting in a decrease in the toughness of the weld metal. Therefore, the Mn content with respect to the total wire mass should be 0.5% by mass or more, preferably 0.7% by mass or more, and more preferably 0.8% by mass or more. On the other hand, when the Mn content with respect to the total wire mass exceeds 2.0% by mass, the high-temperature strength of the weld metal deteriorates. Also, the solidification temperature of the segregation part decreases, the transformation point decreases, and PWHT at high temperature becomes difficult. Therefore, the Mn content with respect to the total wire mass should be 2.0% by mass or less, preferably 1.8% by mass or less, and more preferably 1.6% by mass or less.

[0024] <Cr: 8.0% by mass or more and 11.0% by mass or less> Cr is a major element of 9Cr steel targeted by the flux-cored wire according to this embodiment and is an essential element for ensuring the oxidation resistance and high-temperature strength of the weld metal. If the Cr content with respect to the total mass of the wire is less than 8.0% by mass, the oxidation resistance and high-temperature strength will be insufficient. Therefore, the Cr content with respect to the total mass of the wire should be 8.0% by mass or more, preferably 8.3% by mass or more, and more preferably 8.5% by mass or more. On the other hand, since Cr is a ferrite-forming element, if the Cr content with respect to the total mass of the wire exceeds 11.0% by mass, it will cause the residual of δ-ferrite and deteriorate the toughness and creep performance of the weld metal. Therefore, the Cr content with respect to the total mass of the wire should be 11.0% by mass or less, preferably 10.5% by mass or less, and more preferably 10.0% by mass or less.

[0025] <Ni: 0.05% by mass or more and 1.0% by mass or less> Ni is an austenite-forming element like Mn, and has the effect of suppressing the residual of δ-ferrite in the weld metal and improving the toughness. If the Ni content with respect to the total mass of the wire is less than 0.05% by mass, the effect of improving the toughness of the weld metal cannot be fully obtained. Therefore, the Ni content with respect to the total mass of the wire should be 0.05% by mass or more, preferably 0.1% by mass or more, and more preferably 0.2% by mass or more. On the other hand, if the Ni content with respect to the total mass of the wire exceeds 1.0% by mass, the high-temperature strength will decrease, and the transformation point will decrease, making PWHT at high temperatures difficult. Therefore, the Ni content with respect to the total mass of the wire should be 1.0% by mass or less, preferably 0.8% by mass or less, and more preferably 0.7% by mass or less.

[0026] <Total amount of Mn and Ni: 0.7% by mass or more and 2.5% by mass or less> As described above, both Mn and Ni are elements that have the effect of suppressing the residual δ-ferrite in the weld metal and improving toughness. By appropriately controlling the total content of these elements, a decrease in the transformation point can be suppressed, and PWHT can be carried out at the assumed temperature. Therefore, the total amount of Mn and Ni with respect to the total mass of the wire is preferably 0.7% by mass or more, more preferably 0.9% by mass or more. Also, the total amount of Mn and Ni with respect to the total mass of the wire is preferably 2.5% by mass or less, more preferably 2.2% by mass or less.

[0027] <Mo: 0.7% by mass or more and 1.5% by mass or less> Mo is a solid solution strengthening element and has the effect of improving the creep rupture strength. If the Mo content with respect to the total mass of the wire is less than 0.7% by mass, the desired creep rupture strength cannot be obtained. Therefore, the Mo content with respect to the total mass of the wire is 0.7% by mass or more, preferably 0.75% by mass or more, and more preferably 0.8% by mass or more. On the other hand, if the Mo content with respect to the total mass of the wire exceeds 1.5% by mass, it causes the residual of δ-ferrite and the toughness and creep performance of the weld metal decrease. Therefore, the Mo content with respect to the total mass of the wire is 1.5% by mass or less, preferably 1.3% by mass or less, and more preferably 1.1% by mass or less.

[0028] <Co: 0.10% by mass or more and 1.50% by mass or less> Co is an austenite forming element and has the effect of suppressing the residual δ-ferrite. Although the effect of suppressing the residual δ-ferrite can also be obtained by containing Mn and Ni in the wire, Co has a smaller decrease in the transformation point compared to Mn and Ni, so PWHT can be carried out at high temperature, and the toughness of the weld metal can be improved more effectively, and the creep strength can be improved. If the Co content relative to the total mass of the wire is less than 0.10% by mass, the effect of improving toughness cannot be fully obtained. Therefore, the Co content relative to the total mass of the wire is 0.10% by mass or more, preferably 0.12% by mass or more, more preferably 0.15% by mass or more, still more preferably 0.20% by mass or more, and particularly preferably 0.25% by mass or more. On the other hand, if the Co content relative to the total mass of the wire exceeds 1.50% by mass, the transformation point decreases, and PWHT at high temperatures becomes difficult. Also, since Co is an expensive material, the raw material cost of the wire increases. Therefore, the Co content relative to the total mass of the wire is 1.50% by mass or less, preferably 1.20% by mass or less, more preferably 1.00% by mass or less, still more preferably 0.70% by mass or less, and particularly preferably 0.50% by mass or less.

[0029] <Nb: 0.01% by mass or more and 0.15% by mass or less> Nb is an element that has the effect of improving the strength of the weld metal by solid solution strengthening and also has the effect of contributing to the stabilization of the creep rupture strength by precipitating as nitrides. If the Nb content relative to the total mass of the wire is less than 0.01% by mass, the effects of improving the strength of the weld metal and stabilizing the creep rupture strength cannot be fully obtained. Therefore, the Nb content relative to the total mass of the wire is 0.01% by mass or more, preferably 0.015% by mass or more, and more preferably 0.02% by mass or more. On the other hand, if the Nb content relative to the total mass of the wire exceeds 0.15% by mass, it causes the retention of δ-ferrite, the toughness of the weld metal decreases, and the creep performance deteriorates. Therefore, the Nb content relative to the total mass of the wire is 0.15% by mass or less, preferably 0.12% by mass or less, and more preferably 0.10% by mass or less.

[0030] <V: 0.1% by mass or more and 0.5% by mass or less> V is an element that precipitates in the weld metal as a carbonitride and has the effect of stabilizing the creep rupture strength by precipitation strengthening. If the V content based on the total mass of the wire is less than 0.1% by mass, the desired creep rupture strength cannot be obtained. Therefore, the V content based on the total mass of the wire is 0.1% by mass or more, preferably 0.15% by mass or more, and more preferably 0.17% by mass or more. On the other hand, if the V content based on the total mass of the wire exceeds 0.5% by mass, it causes the remaining of δ-ferrite, deteriorates the toughness of the weld metal, and degrades the creep performance. Therefore, the V content based on the total mass of the wire is 0.5% by mass or less, preferably 0.4% by mass or less, and more preferably 0.3% by mass or less.

[0031] <N: 0.015% by mass or more and 0.060% by mass or less> N is an element that has the effect of improving the strength of the weld metal by solid solution strengthening and also has the effect of contributing to the stabilization of the creep rupture strength by precipitating as a nitride. If the N content based on the total mass of the wire is less than 0.015% by mass, the effects of improving the strength of the weld metal and stabilizing the creep rupture strength cannot be sufficiently obtained. Therefore, the N content based on the total mass of the wire is 0.015% by mass or more, preferably 0.018% by mass or more, and more preferably 0.020% by mass or more. On the other hand, if the N content based on the total mass of the wire is excessive, it does not dissolve in the weld metal and blowholes are generated. Therefore, the N content based on the total mass of the wire is 0.060% by mass or less, preferably 0.050% by mass or less, and more preferably 0.040% by mass or less.

[0032] <Li: 0.11% by mass or less (including 0% by mass)> Li is an element that has the effect of reducing the yield of alloying elements in the wire into the weld metal. In the flux-cored wire according to the present embodiment, since the TiO2 content as a slag former is high, the Ti content in the weld metal tends to be high. Therefore, by containing Li in the wire, the excessive yield of Ti can be suppressed, the increase in excessive strength can be suppressed, and the toughness can be improved. In the present embodiment, the lower limit of the Li content is not particularly limited and may be 0% by mass. However, when Li is contained in the wire for the purpose of suppressing the excessive yield of TiO2, the Li content with respect to the total mass of the wire is preferably 0.02% by mass or more, and more preferably 0.03% by mass or more. On the other hand, when the Li content with respect to the total mass of the wire exceeds 0.11% by mass, the Ti in the weld metal decreases, and the tensile strength of the weld metal decreases. In addition, since the viscosity of the slag decreases, the vertical welding workability deteriorates significantly. Therefore, the Li content with respect to the total mass of the wire is 0.11% by mass or less, preferably 0.09% by mass or less, and more preferably 0.07% by mass or less.

[0033] <Mg: 0.85% by mass or less (including 0% by mass)> Mg is an element that has a deoxidizing effect and contributes to the stabilization of the toughness of the weld metal. In the present embodiment, the lower limit of the Mg content is not particularly limited and may be 0% by mass. When Mg is contained in the wire for the purpose of adjusting the toughness of the weld metal to a desired range, the Mg content with respect to the total mass of the wire may be 0.1% by mass or more or 0.2% by mass or more. On the other hand, when the Mg content with respect to the total mass of the wire exceeds 0.85% by mass, the yield of alloying elements into the weld metal increases, leading to an excessive increase in strength. In addition, the amount of spatter generated increases, and the welding workability deteriorates. Therefore, the Mg content with respect to the total mass of the wire is 0.85% by mass or less, preferably 0.70% by mass or less, and more preferably 0.65% by mass or less.

[0034] <Total amount of K and Na: 0.3 mass% or less (including 0 mass%)> K and Na are components having the effect of stabilizing the arc, and by adding them to the wire in an appropriate amount, a good bead shape can be obtained. In this embodiment, the lower limit of the total amount of K and Na is not particularly limited and may be 0 mass%, but when either one or both of K and Na are contained in the wire for the purpose of further stabilizing the arc, the total amount of K and Na with respect to the total mass of the wire is preferably 0.03 mass% or more, and more preferably 0.05 mass% or more. On the other hand, when the total amount of K and Na with respect to the total mass of the wire exceeds 0.3 mass%, the toughness of the weld metal decreases. Therefore, the total amount of K and Na with respect to the total mass of the wire is 0.3 mass% or less, preferably 0.2 mass% or less, and more preferably 0.15 mass% or less. Note that the wire according to this embodiment may contain both K and Na or only one of them, as long as the total amount is within the above range.

[0035] <P: 0.020 mass% or less (including 0 mass%)> P is an element that increases the susceptibility to hot cracking. When the P content with respect to the total mass of the wire exceeds 0.020 mass%, hot cracking occurs. Therefore, the P content with respect to the total mass of the wire is 0.020 mass% or less, preferably 0.015 mass% or less, and more preferably 0.012 mass% or less.

[0036] <S: 0.020 mass% or less (including 0 mass%)> S is an element that increases the susceptibility to hot cracking. When the S content with respect to the total mass of the wire exceeds 0.020 mass%, hot cracking occurs. Therefore, the S content with respect to the total mass of the wire is 0.020 mass% or less, preferably 0.018 mass% or less, and more preferably 0.015 mass% or less.

[0037] In addition, it is preferable that the wire according to this embodiment contains the Li content of 0.01 mass % or more and 0.11 mass % or less, and the ratio of the TiO2 content to the Li content in the wire is appropriately controlled.

[0038] <[TiO2] / [Li]:70 or more and 170 or less> In this embodiment, TiO2 is contained in the wire to improve the workability in all-position welding, but when Ti from TiO2 is contained in the weld metal, the tensile strength becomes excessive and the toughness decreases. As described above, Li has the effect of suppressing the yield of Ti in the weld metal, but the excessive Li contained in the wire leads to a decrease in tensile strength. Therefore, it is preferable to set the Li content within a predetermined range and control it by the TiO2 content. That is, by controlling the ratio of the TiO2 content to the Li content within a predetermined range, the balance between the strength and toughness of the weld metal can be improved. The upper limit of the Li content is as described above. In order to achieve a good balance between the strength and toughness of the weld metal, when the ratio of the TiO content to the Li content is controlled, the Li content with respect to the total mass of the wire is preferably 0.01 mass% or more.

[0039] Furthermore, when the TiO2 content in the wire is expressed as [TiO2] in mass% relative to the total mass of the wire, and the Li content in the wire is expressed as [Li] in mass% relative to the total mass of the wire, a decrease in tensile strength can be suppressed by making the value obtained from the formula ([TiO2] / [Li]) 70 or more. Therefore, the value obtained from the formula ([TiO2] / [Li]) is preferably 70 or more, more preferably 75 or more, and even more preferably 80 or more. On the other hand, the decrease in toughness can be suppressed by setting the value obtained from the formula ([TiO2] / [Li]) to 170 or less. Therefore, the value obtained from the formula ([TiO2] / [Li]) is preferably 170 or less, more preferably 160 or less, and even more preferably 150 or less.

[0040] In addition, the wire according to the present embodiment preferably further contains F (fluoride) within the content range shown below. The reasons for limiting the content when F is contained in the wire will be described below.

[0041] <F: 0.10 mass% or more and 0.60 mass% or less> F is not an essential component in the wire of the present embodiment, but is an element having an effect of reducing the diffusible hydrogen content in the weld metal, and F can be contained in the wire as an optional component. When the F content with respect to the total mass of the wire is 0.10 mass% or more, the diffusible hydrogen content can be reduced and the occurrence of cracks can be suppressed. Therefore, when F is contained in the wire, the F content with respect to the total mass of the wire is preferably 0.10 mass% or more, more preferably 0.15 mass% or more, still more preferably 0.17 mass% or more, and particularly preferably 0.20 mass% or more. On the other hand, when the F content with respect to the total mass of the wire is 0.60 mass% or less, an increase in spatter can be suppressed and the arc can be stabilized. Therefore, when F is contained in the wire, the F content with respect to the total mass of the wire is preferably 0.60 mass% or less, more preferably 0.55 mass% or less, and still more preferably 0.50 mass% or less.

[0042] Furthermore, the wire according to the present embodiment preferably contains at least one selected from Al2O3, metallic Zr, and Zr compounds within the content ranges shown below. The reasons for limiting the respective contents when these components are contained in the wire will be described below.

[0043] <Al2O3: 0.50 mass% or less> Al2O3 is a slag former and is not an essential component in the wire of the present embodiment, but can improve the bead shape, so Al2O3 can be contained in the wire as an optional component. When Al2O3 is contained in the wire, the content of Al2O3 relative to the total mass of the wire is preferably 0.02 mass% or more, and more preferably 0.03 mass% or more. On the other hand, when the Al2O3 content relative to the total mass of the wire is 0.50 mass% or less, good slag removability can be obtained. Therefore, when Al2O3 is contained in the wire, the Al2O3 content relative to the total mass of the wire is preferably 0.50 mass% or less, more preferably 0.40 mass% or less, and even more preferably 0.30 mass% or less. In this embodiment, the Al2O3 content is the Al2O3 equivalent value of Al compounds. More specifically, the Al2O3 content is the value of all Al that is insoluble in acid, converted into Al2O3.

[0044] <ZrO2 equivalent value of metallic Zr and Zr compounds: 0.50 mass% or less> ZrO2 is a component having a deoxidizing effect and is not an essential component in the wire of this embodiment, but since it can improve the bead toe shape, ZrO2 can be contained in the wire as an optional component. When ZrO2 is contained in the wire, the ZrO2 content relative to the total mass of the wire is preferably 0.05 mass% or more, and more preferably 0.07 mass% or more. On the other hand, if the ZrO2 content relative to the total mass of the wire is 0.50 mass% or less, the fluidity of the slag can be kept appropriate. Therefore, when ZrO2 is contained in the wire, the ZrO2 content relative to the total mass of the wire is preferably 0.50 mass% or less, more preferably 0.35 mass% or less, and even more preferably 0.30 mass% or less. In this embodiment, the ZrO2 equivalent value refers to the ZrO2 equivalent value obtained by converting all Zr contained in the wire, including simple Zr and Zr alloys, and originating from metallic Zr and Zr compounds, into ZrO2.

[0045] Furthermore, the wire according to the present embodiment preferably contains Al within the range of the content shown below. The reason for limiting the content when Al is contained in the wire will be described below.

[0046] <Al: 0.20 mass% or less> Al is a component having a deoxidizing effect and is not an essential component in the wire of the present embodiment. However, since it can stabilize the toughness of the weld metal, Al can be contained in the wire as an optional component. When Al is contained in the wire, the Al content with respect to the total mass of the wire is preferably 0.01 mass% or more, and more preferably 0.02 mass% or more. On the other hand, when the Al content with respect to the total mass of the wire is 0.20 mass% or less, the yield of alloying elements into the weld metal can be appropriately adjusted, and an excessive increase in strength can be suppressed. Therefore, when Al is contained in the wire, the Al content with respect to the total mass of the wire is preferably 0.20 mass% or less, more preferably 0.12 mass% or less, and even more preferably 0.10 mass% or less. In the present embodiment, the Al content is the total amount of Al contained in Al alone and Al alloys.

[0047] <Remainder> The flux-cored wire according to the present embodiment contains inevitable impurities in the range of 1.5 mass% or less with respect to the total mass of the wire as the remainder of the components other than the above. Also, the remainder of the wire may contain Cu, Ca, W, B, etc. The flux-cored wire according to the present embodiment may be contained, for example, in the range of Cu: 0.30 mass% or less, Ca: 0.05 mass% or less, W: 0.1 mass% or less, B: 0.05 mass% or less. Also, metallic Ti may be contained in an amount of 0.20 mass% or less, and may be 0.10 mass% or less, 0.05 mass% or less, 0.01 mass% or less. Here, metallic Ti is Ti alone or a Ti alloy, and means the content of Ti soluble in an acid.

[0048] Furthermore, the flux-cored wire according to this embodiment preferably contains the above-mentioned total amounts of Fe, C, TiO2, SiO2 equivalents, Mn, Cr, Ni, Mo, Co, Nb, V, N, Li, Mg, K and Na, P and S in a total amount of 90 mass% or more, more preferably 93 mass% or more, even more preferably 96 mass% or more, and particularly preferably 98 mass% or more, based on the total mass of the wire.

[0049] The outer diameter of the flux-cored wire in this embodiment is not particularly limited, but is preferably, for example, 0.9 mm or more and 1.6 mm or less. The flux filling rate of the flux-cored wire in this embodiment can be set to any value as long as the content of each element in the wire is within the range of the present invention. However, from the viewpoint of drawability and wire feedability during wire production, it is preferable to set the flux filling rate to, for example, 15 mass % or more and 25 mass % or less with respect to the total mass of the wire. In the flux-cored wire of the present embodiment, the outer sheath may have a joint or may not have a joint, and there is no limitation on the form of the joint or the shape of the cross section. The flux-cored wire of the present embodiment can be used for gas-shielded arc welding using a mixed gas of, for example, 80% by volume Ar and 20% by volume CO2 as a shielding gas.

[0050] [2. Manufacturing method of flux-cored wire] The method for producing the flux-cored wire according to the present embodiment is not particularly limited, but it can be produced, for example, by the method described below. First, a steel strip that constitutes the steel sheath is prepared, and this steel strip is formed into a U-shaped open tube by a forming roll while being fed in the longitudinal direction. Next, a flux containing various raw materials is filled into the steel sheath so as to have a predetermined composition, and then the steel sheath is processed so as to have a circular cross section. Then, the wire is drawn by cold working to obtain the flux-cored wire according to the present embodiment. Annealing may be performed during the cold working. Either a seamless wire in which the seams of the steel sheath formed during the manufacturing process are welded, or a wire in which the seams are not welded and are left as gaps can be used. EXAMPLES

[0051] The effects of the present invention will be specifically described below with reference to examples of the present invention and comparative examples, but the present invention is not limited thereto.

[0052] The wire components were adjusted to have various contents, and flux-cored wires with a diameter of 1.2 mm were produced.

[0053] <Evaluation of diffusible hydrogen content> Using the prepared flux-cored wire, gas-shielded arc welding was performed under the welding conditions for the evaluation test of the amount of diffusible hydrogen shown in Table 1 below, and the amount of diffusible hydrogen was measured in accordance with the "Method of measuring hydrogen content in steel welds" specified in JIS Z 3118: 2007. The wire extension length was 25 mm. The evaluation criteria for the amount of diffusible hydrogen were as follows: 4 (ml / 100g) or less was rated as A (excellent), and over 4 (ml / 100g) was rated as B (good).

[0054] <Evaluation of mechanical properties> Using the prepared flux-cored wire, MAG (Metal Active Gas) welding was performed under the welding conditions for the mechanical property evaluation test shown in Table 1 below, and then PWHT was performed to prepare a weld metal test specimen. The mechanical properties of the weld metal were evaluated in accordance with "Tensile and impact test method for weld metal" specified in JIS Z 3111:2005, and A2 tensile test specimens were taken from the weld metal test specimens to evaluate "tensile strength" by a tensile test, and V-notch test specimens were taken to evaluate "toughness" by a Charpy impact test at 20℃. The mechanical properties were evaluated based on the following criteria: tensile strength of 750 MPa or more was rated as A (excellent), 700 MPa or more but less than 750 MPa was rated as B (good), and less than 700 MPa was rated as C (poor). Regarding toughness, those with a Charpy impact value of 25J or more at 20°C were rated as A (excellent), those with a Charpy impact value of 20J or more but less than 25J were rated as B (good), and those with a Charpy impact value of less than 20J were rated as C (poor).

[0055] <Welding workability evaluation> In order to evaluate the welding workability, gas-shielded arc welding was performed using the above flux-cored wire under the welding conditions for the evaluation test of the welding workability shown in the following Table 1. In this example, two types of welding positions were used: horizontal fillet welding and vertical upward fillet welding. The evaluation criteria for welding workability were based on visual observation of bead fit, the presence or absence of extremely convex beads, the amount of spatter, and sagging. Those that were excellent in all respects were given an A (excellent), those that were inferior but could be used without problems were given a B (good), and those that were difficult to use were given a C (poor).

[0056] Next, the component compositions of the produced wires and calculated values ​​based on specific components are shown in Tables 2 and 3 below, and the evaluation results are also shown in Table 3 below. The main component is Fe in the components shown in "Wire Components" in Tables 2 and 3. The total of the components shown in Tables 2 and 3 and Fe in each wire is 99 mass % or more. In addition, in Table 3, [TiO2] is the value of the TiO2 content in the wire expressed as mass% relative to the total mass of the wire, and [Li] is the value of the Li content in the wire expressed as mass% relative to the total mass of the wire. Furthermore, in the wire composition columns in Tables 2 and 3, "-" indicates that the corresponding component was not actively added during the manufacture of the wire. Furthermore, in the evaluation results column in Table 3, "-" indicates that the corresponding evaluation test was not performed.

[0057] [Table 1]

[0058] [Table 2]

[0059] [Table 3]

[0060] As shown in Tables 2 and 3 above, Wire Nos. 1 to 14, which are examples of the invention, had excellent mechanical properties, welding workability, and diffusible hydrogen content because the wire compositions were within the ranges of the present invention. In addition, although not shown in Table 3, Wire Nos. 1 to 14, which are examples of the invention, had excellent creep rupture strength because the Cr, Mo, Co, Nb, V, and N contents in the wire were within the ranges of the present invention. Furthermore, the inventive examples of Wire Nos. 1 to 10 had excellent evaluation results for the amount of diffusible hydrogen because the F content was within the preferred range of the present invention. Although the inventive examples of Wire Nos. 11 and 12 were not subjected to an evaluation test for the amount of diffusible hydrogen, it is presumed that, like Wire Nos. 1 to 10, the F content was within the preferred range of the present invention and therefore excellent evaluation results for the amount of diffusible hydrogen were obtained.

[0061] On the other hand, in the case of Wire No. 15, which is a comparative example, the Li content exceeded the upper limit of the range of the present invention, so the viscosity of the slag decreased, and the sagging resistance in the vertical weld advance was significantly deteriorated. In addition, the Ti yield in the weld metal decreased, and the tensile strength also decreased. In the comparative example, Wire No. 16, the Co content in the wire was below the lower limit of the range of the present invention, and therefore the toughness was reduced. Furthermore, as a result of observing the structure of the weld metal, it was confirmed that δ ferrite remained.

[0062] Wire Nos. 17 and 19, which are comparative examples, had reduced toughness because the Mg content and the total amount of K and Na in the wire exceeded the upper limit of the range of the present invention.

[0063] The comparative examples, Wire Nos. 18 and 20, had reduced toughness because the Mg content in the wire exceeded the upper limit of the range of the present invention. In the comparative example wires No. 21 and 23 to 25, the TiO2 content in the wire was below the lower limit of the range of the present invention, and the SiO2 equivalent value exceeded the upper limit of the range of the present invention, so that the welding workability was deteriorated.

[0064] In the case of Wire No. 22, which is a comparative example, the TiO2 content in the wire was below the lower limit of the range of the present invention, and therefore the welding workability was degraded. Wire No. 26, which is a comparative example, had a Mg content exceeding the upper limit of the range of the present invention, and therefore produced a lot of spatter and deteriorated welding workability.

[0065] As described above in detail, it has been shown that, according to the flux-cored wire according to the present embodiment, even when PWHT is performed at 760°C, a weld metal excellent in strength and toughness can be obtained, and the welding workability is good.

Claims

[Claim 1] A flux-cored wire for gas shielded arc welding, the wire having a steel sheath filled with flux, For the total mass of wire, Fe: 75% by mass or more and 85% by mass or less, C: 0.05% by mass or more and 0.25% by mass or less, TiO 2 : 3.0% by mass or more and 9.0% by mass or less (wherein the TiO 2 is the value obtained by converting all Ti that is insoluble in acid into TiO 2 ), Metallic Si and Si compound SiO 2 Conversion value: 0.5% by mass or more and 1.5% by mass or less, Mn: 0.5% by mass or more and 2.0% by mass or less, Cr: 8.0% by mass or more and 11.0% by mass or less, Ni: 0.05% by mass or more and 1.0% by mass or less, Mo: 0.7% by mass or more and 1.5% by mass or less, Co: 0.10% by mass or more and 1.50% by mass or less, Nb: 0.01% by mass or more and 0.15% by mass or less, V: 0.1% by mass or more and 0.5% by mass or less, N: 0.015% by mass or more and 0.060% by mass or less Li: 0.01% by mass or more and 0.11% by mass or less, F: 0.10% by mass or more and 0.60% by mass or less; Mg: 0.85% by mass or less, Total amount of K and Na: 0.3 mass% or less, P: 0.020% by mass or less, S: 0.020% by mass or less, Al: 0.20% by mass or less, Cu: 0.30% by mass or less, Ca: 0.05% by mass or less, W: 0.1% by mass or less, B: 0.05% by mass or less, Metal Ti: 0.20% by mass or less (wherein the metal Ti is the content of Ti soluble in acid), Inevitable impurities: 1.5% by mass or less; Furthermore, at least one selected from Al 2 O 3 , metallic Zr, and a Zr compound is added to the total mass of the wire. Al2O3: 0.50% by mass or less, The content of metallic Zr and Zr compounds is in the range of 0.50 mass% or less in terms of ZrO2, Furthermore, the TiO 2 content in the wire is expressed as [TiO 2 ] in mass % relative to the total mass of the wire; When the Li content in the wire is expressed as [Li] in mass% relative to the total mass of the wire, [TiO 2 ] / [Li]: 70 or more and 170 or less; A flux-cored wire characterized in that the total amount of Fe, C, TiO2, the SiO2 equivalent value, Mn, Cr, Ni, Mo, Co, Nb, V, N, Li, Mg, K and Na, P and S is 96 mass% or more based on the total mass of the wire.

Citation Information

Patent Citations

  • Flux cored wire for mag welding of 9 cr-1 mo-v-nb steel

    JP1999207490A

  • Flux-cored wire for gas shielded arc welding

    JP2015027700A

  • Flux-cored wire for gas shield arc welding, and method for production of weld joint

    JP2018144071A

  • Flux-cored wire for gas shield arc-welding, and method of manufacturing weld joint

    JP2019048324A

  • Flux-cored wire for gas shield arc welding, and welding method

    JP2019093428A